Efeito da fragmentação no metabolismo energético e nível trófico em duas espécies de morcegos frugívoros, Artibeus lituratus e Carollia perspicillata (Chiroptera: Phyllostomidae) - Muñoz-Lazo, Fernando Julio João [UNESP] (2013)
We estimated the relative contribution of fruits and insects as protein source in the diet of two species of frugivorous bats (Artibeus lituratus and Carollia perspicillata) through the use of stable isotopes of carbon (13C) and nitrogen (15N). The contribution of insects as protein source in the diet was prevalent in both species. In A. lituratus, the contribution of insects was 95 percent in fragmented area, and 75 percent in continuous area. However, in C. perspicilllata, the contribution of insects was 85 percent in fragmented area, and 98 percent in continuous area. In spite of differences in the trophic level between A. lituratus and C. perspicilllata, they are very similar to each other, indicating that both species are found in the same trophic position along the food chain. For each species have been tested 15 mathematical models to determine whether basal metabolic rate (BMR) is explained by body mass, trophic level, net primary productivity and temperature. In A. lituratus, four models were mathematically plausible in explaining the basal metabolic rate, two of these models explained TMB in terms of net primary productivity, and trophic level. In C. perspicillata, two models explained the TMB, one of these models explained TMB in terms of body mass, net primary productivity, and ambient temperature. Our result seems to support the food habits hypotheses in A. lituratus and C. perspicilllata